Meningkatan Pemahaman Literasi dan Numerasi Siswa SMP NU Sunan Giri Kepanjen melalui Festival Literasi dan Numerasi - Indhira Anggista; Sinollah (Jurnal Pengabdian Masyarakat: Tipis Wiring, 2025)
This community service activity aims to improve the literacy and numeracy understanding of students at SMP NU Sunan Giri Kepanjen through the Literacy and Numeracy Festival “Kartini Edufest”. This program integrates a descriptive qualitative approach in the analysis of literature and field data. Data collection methods include observation, interviews, and documentation. The results of the activity showed an increase in student enthusiasm and participation in literacy and numeracy activities. This festival also succeeded in fostering students' entrepreneurial spirit and creativity. Although there was an increase in students' literacy and numeracy skills, there were several factors that influenced the optimization of the results. This community service activity made a positive contribution in developing student competencies and is expected to be a model for similar activities in the future.